Economic Burden of Atopic Dermatitis in Taiwan - Ellen M. Lee; Yung-Tsu Cho; Tom C. Chan; Dereck Shen; Chia-Yu Chu; Chao-Hsiun Tang (Medical Journals Sweden, 2023)
Atopic dermatitis is a prevalent inflammatory skin disease that manifests clinically as pruritus and eczema. Severe forms of atopic dermatitis can be chronic and relapsing or associated with other dermatological complications and comorbidities, resulting in lifelong impacts across multiple aspects for patients. This study was conducted to calculate the atopic dermatitis-related economic burden in Taiwan. First, the out-of- pocket costs incurred by 200 patients with atopic dermatitis were estimated using a specifically designed questionnaire. Secondly, work impairment was converted into quantifiable costs. The costs reimbursed by the Taiwan National Health Insurance (NHI), which were estimated in our previous work, were included in the final calculation. The atopic dermatitis-related economic burden for patients in Taiwan in 2018 was estimated as (2018 New Taiwan dollars; NT$) 37.90 billion, which is 0.207% of Taiwan's gross domestic product. This substantial economic burden suggests an existing need for more effective and equitable treatment for atopic dermatitis.